2013
DOI: 10.1021/ac400077e
|View full text |Cite
|
Sign up to set email alerts
|

Application of GC-MS/MS for the Analysis of Tobacco Alkaloids in Cigarette Filler and Various Tobacco Species

Abstract: This publication reports the first known use of gas chromatography-tandem mass spectrometry for the quantitation of five minor tobacco alkaloids (nornicotine, myosmine, anabasine, anatabine and isonicoteine) in various tobacco samples. A summary of the concentrations of these minor alkaloid levels in the filler from 50 popular cigarette brands were found to be 659 -986 μg/g nornicotine, 8.64 -17.3 μg/g myosmine, 127 -185 μg/g anabasine, 927 -1390 μg/g anatabine, and 23.4 -45.5 μg/g isonicoteine. Levels of mino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 19 publications
2
79
0
Order By: Relevance
“…Observed differences in alkaloid content are most likely due to the variations in cigarette filler composition. Overall, the results on the determination of nicotine and three minor alkaloids obtained in this study compare well within ranges reported for similar products in other studies [7,31,32]. Proposed HILIC-MS/MS technique offers distinct advantages over previous methods, including unambiguous analyte identification, ease of sample preparation, enhanced sensitivity, and high throughput.…”
Section: Analytical Performancesupporting
confidence: 86%
“…Observed differences in alkaloid content are most likely due to the variations in cigarette filler composition. Overall, the results on the determination of nicotine and three minor alkaloids obtained in this study compare well within ranges reported for similar products in other studies [7,31,32]. Proposed HILIC-MS/MS technique offers distinct advantages over previous methods, including unambiguous analyte identification, ease of sample preparation, enhanced sensitivity, and high throughput.…”
Section: Analytical Performancesupporting
confidence: 86%
“…It grows well in warm-arid and semiarid climates on marginal unfertile lands (Biblioteca digital de la medicina tradicional Mexicana, 2009). High levels of anabasine, a piperidine alkaloid isomer of nicotine, have been reported in this plant as far as 1935 (Smith, 1935;Galiana and VigueraLoko, 1964), and confirmed in many other chemical studies (Lisko et al, 2013). Ingestion of this alkaloid can result in severe or lethal poisoning in humans, livestock and poultries (Papavisiliu and Heliakis, 1947;Castorena et al, 1987;Sims et al, 1999;Mizrachi et al, 2000;Schep et al, 2009;Botha et al, 2011;Semmler et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
“…These impurities and degradation products (structures shown in Figure 1) can be transferred to the aerosol and subsequently to the user of the device. There are many methods for the analysis of nicotine and related alkaloids including gas chromatography coupled with flame ionization detection (FID) (6, 7), nitrogenphosphorus detection (NPD) (8), and mass spectrometry (MS) (9). However, methods for the analysis of nicotine in tobacco smoke and products may not be suitable for e-liquids and aerosols since several of the nicotine related compounds such as nicotine-N-oxide, are known to be thermally unstable at temperatures required for GC analysis.…”
Section: Introductionmentioning
confidence: 99%